2006
DOI: 10.1523/jneurosci.2773-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gq-Protein-Coupled Inositol Trisphosphate and Ca2+Signaling by the Membrane Potential

Abstract: G q protein-coupled receptors (G q PCRs) are widely distributed in the CNS and play fundamental roles in a variety of neuronal processes. Their activation results in PIP 2 hydrolysis and Ca 2+ release from intracellular stores via the PLC-IP 3 signaling pathway. Since early G q PCR signaling events occur at the plasma membrane of neurons, they might be influenced by changes in membrane potential. In this study we use combined patch-clamp and imaging methods to investigate whether membrane potential changes can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 72 publications
(109 reference statements)
3
51
0
1
Order By: Relevance
“…Because M 2 and M 4 are coupled to G i/o proteins, stimulation of these two subtypes can inhibit synaptic glutamate release through inhibition of voltage-gated calcium channels (40 -42). On the other hand, M 3 and M 5 are coupled to G q/11 proteins, and activation of these two subtypes could increase presynaptic glutamate release through stimulation of phospholipase Cinositol triphosphate, which increase the intracellular calcium level (43,44). It would be interesting to determine whether M 3 /M 5 stimulation "antagonizes" the muscarinic analgesic effect at the spinal level by comparing the effects of mAChR agonists on nociception in WT, M 3 -KO, and M 5 -KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Because M 2 and M 4 are coupled to G i/o proteins, stimulation of these two subtypes can inhibit synaptic glutamate release through inhibition of voltage-gated calcium channels (40 -42). On the other hand, M 3 and M 5 are coupled to G q/11 proteins, and activation of these two subtypes could increase presynaptic glutamate release through stimulation of phospholipase Cinositol triphosphate, which increase the intracellular calcium level (43,44). It would be interesting to determine whether M 3 /M 5 stimulation "antagonizes" the muscarinic analgesic effect at the spinal level by comparing the effects of mAChR agonists on nociception in WT, M 3 -KO, and M 5 -KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the well-known fact that M 3 Rs, but not M 2 Rs and M 1 Rs, normally provide predominant neuronal control of Ca 2ϩ and contractile responses in SMCs. Billups et al have shown that voltage depolarization significantly increases the muscarinic agonist oxotremorine-evoked Ca 2ϩ release by augmenting IP 3 production in neurons (14). It is also known that membrane depolarization can affect other multiple GPCRdependent signaling cascade sites to enhance muscarinic agonistinduced Ca 2ϩ release in a variety of cells (8).…”
Section: Membrane Depolarization Induces Ca 2؉ Release Through Ryanodinementioning
confidence: 99%
“…The remaining Ca 2ϩ release pathway from the ER involves IP 3 -sensitive receptors. Interestingly, it has been shown recently in cerebellar granule neurons that depolarization alone can activate phospholipase C (PLC) via G q -proteins, leading to phosphatidylinositol-4,5-biphosphate hydrolysis and IP 3 production in a mechanism completely independent of Ca 2ϩ influx (Billups et al, 2006). To block IP 3 -mediated Ca 2ϩ release, we used the widely used IP 3 channel blocker 2-APB.…”
Section: Electrical Activity Causes Fast Growth Cone Stallingmentioning
confidence: 99%